STUDYING THE AWARENESS, ATTITUDE AND PRACTICE OF ADMINISTRATIVE STAFF ON EDUCATIONAL QUALITY ASSESSMENT ACTIVITIES AT HANOI MEDICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2026)
Objective: The study aims to assess the level of awareness, attitude and practice of administrative staff towards educational quality assessment activities at Hanoi Medical University. Method: A cross-sectional descriptive study was conducted on 152 administrative staff (out of a total of 439 administrative staff) working at Hanoi Medical University. Data were collected through structured questionnaires and analyzed using R software with descriptive statistics to reflect the current state of awareness, attitudes, and level of participation of administrative staff in educational quality accreditation activities. Results: 62.7% of staff had a correct understanding of educational quality accreditation, 74.0% had a positive attitude, but only 48.7% practiced correctly; The results show that staff had a positive attitude towards accreditation activities, however, the level of practical participation and theoretical knowledge was still uneven among different groups of staff. Recommendations: Internal communication programs and specialized training should be strengthened to raise awareness and practice of educational quality assessment within the school administration.
Keywords: quality control, administration, awareness, attitude, practice.